Peaceful End Of Life Of Aids Patients In The Group Support Peers (Kds) Kediri City - Andriono; Sutrisno; Novita Ana Anggraini (Journal of Hospital Management and Services, 2020)
HIV infects white blood cells which causes a decrease in human immunity, making it susceptible to various infections. People with HIV/AIDS (PLWHA) face various symptoms related to HIV for a long time and must struggle to overcome various physical, social, poverty, depression, and cultural beliefs that can affect quality of life . This study focuses on exploring the fulfillment of basic needs based on the concept of peaceful end of life in AIDS patients which include , free from pain , get comfort , get dignity and respect , be at peace and experience closeness to significant others and those who care . The design of this study is qualitative with a narrative study approach. Using purposive sampling technique with a sample of some PLWHA in the Peer Support Group (KDS) of Kediri City totaling 4 informants. Data collection was carried out by in -depth interview with semi-structured interviews, the results were analyzed using an inductive thinking process. The results of the study showed 4 concepts of the Peaceful End of Life theory , namely free from pain , get comfort , get dignity and respect , closeness to significant others and those who care have been fulfilled, 1 concept that has not been fulfilled is being at peace. Peace is a need for every individual, both healthy and sick, especially for people with terminal illnesses such as AIDS. In people with HIV and AIDS (ODHA) in the Peer Support Group (KDS) in Kediri City, this has not been met . This is because because of feelings of fear of death, concerns about their health condition and anxiety about changes in their status in society or in their work environment.